Multi-consensus formation control by artificial potential field based on velocity threshold - Chang, Xiaofei; 焦, 佳玥; Li, Yuenan; Hong, Bei (Frontiers in Neuroscience, 2024)
This paper proposes a multi-consensus formation control algorithm by artificial potential field (APF) method based on velocity threshold. The algorithm improves the multi-consensus technique. This algorithm can split a group of agents into multiple agent groups. Note that the algorithm can easily complete the queue transformation as long as the entire proxy group is connected initially and no specific edges need to be removed. Furthermore, collision avoidance and maintenance of existing communication connectivity should be considered during all agents' movement. Therefore, we design a new swam motion potential function. The stability of multi-consensus formation control has proven to be effective in avoiding collisions, maintaining connectivity, and generating formations. The final numerical simulation results show the role of the controller we designed.